Report on an announced visit to Maghaberry Prison 5 - 7 September 2016, to review progress against the nine inspection recommendations made in 2015. (2016) - Northern Ireland., Criminal Justice Inspectorate,; Northern Ireland., Department of Education., Education and Training Inspectorate,; Great Britain., Her Majesty's Chief Inspector of Prisons for England and Wales,; Northern Ireland., Regulation and Quality Improvement Authority,
No abstract available